2012
DOI: 10.1259/bjr/33224341
|View full text |Cite
|
Sign up to set email alerts
|

Totally implantable venous power ports of the forearm and the chest: initial clinical experience with port devices approved for high-pressure injections

Abstract: Objectives: To evaluate the technical success, clinical outcome and safety of percutaneously placed totally implantable venous power ports (TIVPPs) approved for high-pressure injections, and to analyse their value for arterial phase CT scans. Methods: Retrospectively, we identified 204 patients who underwent TIVPP implantation in the forearm (n5152) or chest (n552) between November 2009 and May 2011. Implantation via an upper arm (forearm port, FP) or subclavian vein (chest port, CP) was performed under sonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 23 publications
4
39
0
Order By: Relevance
“…The forearm group showed a significantly higher incidence of catheter occlusion than the chest group, corresponding to findings reported previously [3,34]. The forearm is located the most peripherally compared to the remaining sites considered in this study and has the longest catheter, which passes the elbow joint, and these factors may affect the occurrence of catheter occlusion at this site.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The forearm group showed a significantly higher incidence of catheter occlusion than the chest group, corresponding to findings reported previously [3,34]. The forearm is located the most peripherally compared to the remaining sites considered in this study and has the longest catheter, which passes the elbow joint, and these factors may affect the occurrence of catheter occlusion at this site.…”
Section: Discussionsupporting
confidence: 87%
“…Central venous port implantation (CVPI) is used in different phases of cancer therapy as it is a secure venous route for treatment (chemotherapy), supportive therapy (e.g., prophylactic agents for chemotherapy-related adverse events and intravenous hyperalimentation), palliative care (e.g., symptom-relieving agents), and other procedures (e.g., blood collection and rapid injection of contrast media for imaging examination [with verified devices]) [1][2][3][4]. Since it enables easy transition of these interventions from the inpatient department to the outpatient department or home, CVPI shortens the length of hospitalization and may consequently reduce the overall cost of healthcare [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A central venous access is mandatory for hyperosmolar, basic (pH ≤4.0), alkaline (pH ≥9.0) and local irritant medication, such as chemotherapy, antibiotics and parenteral nutrition. Moreover, high pressure infusions such as those required for computed tomographic examinations of up to 5 ml/s, as well as blood tests, which can be performed through such selected systems, streamlining workflow and increasing patient quality of life (1)(2)(3).…”
mentioning
confidence: 99%
“…In retrospective studies, venous thrombosis (VT) rate has been found to be statistically higher in patients with arm ports compared with patients with chest ports (11.4% vs 4.8%; n ¼ 440 patients), (9.9% vs 1.9%; n ¼ 204 patients). 23,24 According to a retrospective study by Akahane et al, 25 combined phlebitis and mechanical rates were higher in patients with arm ports (n ¼ 162 patients). In a prospective study 26 (n ¼ 215), VT rates were found to be similar in both patient groups.…”
Section: Complicationsmentioning
confidence: 99%